Back Cover: AIEgen‐enhanced protein imaging: Probe design and sensing mechanisms. Issue 3 (29th June 2021) - Naghibi, Sanaz; Chen, Tong; Jamshidi Ghahfarokhi, Amin; Tang, Youhong
Abstract : Proteins are the building blocks of life, regarded as one of the most complex and crucial biomacromolecules in biological systems, and playing a significant role in executing genes and transferring genetic information. The aggregation induced emission (AIE) concept and its applications for real‐time imaging make AIE luminogens attractive for protein tracking, detecting, and imaging for medical applications. (Article number 2021, 2, e41 )